Biological and quantum computing for human vision holonomic models and applications - Perus, Mitja, 1969-; Loo, Chu Kiong, 1971-; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2011)
"This book presents an integrated model of human image processing and conscious visual experience, based mainly on the Holonomic Brain Theory by Karl Pribram. This work researches possibilities for complementing neural models of early vision with the new preliminary quantum models of consciousness in order to construct a model of human image processing"--Provided by publisher.
Holonomic brain processes -- Computational information-maximization models -- Images, associations, and conscious experience -- Computer simulations and applications of quantum associative network -- Visual processing as described by contemporary main-stream neuroscience -- Comparison of the mathematical formalism of associative ANN and quantum theory -- Derivation of quantum associative network from Hopfield-like ANN and HNeT -- Quantum neural information processing -- Quantum phase-hebbian image -- Computational models relevant for visual cortex -- Hardware implementation relevant for visual cortex.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Keywords: Visual cortex -- Mathematical models; Computational neuroscience; Quantum computers; Neural networks (Neurobiology); Visual Perception -- physiology; Models, Psychological; Quantum Theory; Applications of quantum associative network; Convolution, correlation and matrix-processing; Holonomic brain processing; Holonomic theory of vision; Maximal presentation of information; Quantum associative network; Quantum neural information processing; Retinopic mapping; Holonomic model of visual perception; Visual processing and neuroscience; Electronic books